2014
DOI: 10.1016/j.fuel.2014.04.003
|View full text |Cite
|
Sign up to set email alerts
|

The turbulent burning velocity of methanol–air mixtures

Abstract: Methanol is a sustainable and versatile alternative fuel for spark-ignition engines and other combustion applications. To characterize the combustion behavior of this fuel, a good understanding of the factors affecting its turbulent burning velocity is re-10 quired. This paper presents experimental values of the turbulent burning velocity of methanol-air mixtures obtained in a fan-stirred bomb, for u ′ = 2-6 m/s, φ= 0.8-1.4, T= 358 K and pressures up to 0.5 MPa. In combination with laminar burning velocity val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Learnt from Vancoillie et al, 22 an indicator (t a , the time when the rate of pressure rise reaches to 50%) was used to assess the acceptable level of such smoothing. Learnt from Vancoillie et al, 22 an indicator (t a , the time when the rate of pressure rise reaches to 50%) was used to assess the acceptable level of such smoothing.…”
Section: Data Processing and Parameter Definitionmentioning
confidence: 99%
See 3 more Smart Citations
“…Learnt from Vancoillie et al, 22 an indicator (t a , the time when the rate of pressure rise reaches to 50%) was used to assess the acceptable level of such smoothing. Learnt from Vancoillie et al, 22 an indicator (t a , the time when the rate of pressure rise reaches to 50%) was used to assess the acceptable level of such smoothing.…”
Section: Data Processing and Parameter Definitionmentioning
confidence: 99%
“…Learnt from Vancoillie et al, 22 the variation of t a (of 5%) also could be taken as the criterion to evaluate the repeatability. Learnt from Vancoillie et al, 22 the variation of t a (of 5%) also could be taken as the criterion to evaluate the repeatability.…”
Section: Uncertainty Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, the value of t a (defined as the time to reach a pressure rise of 50%) is around 22.480 ms with a maximum error of about −1.68% (which also exists at Series IV), namely, the uncertainty on ta induced by the systematic factor is about ±1.68. It should be emphasised that, learning from previous scholars [14,15], t a is one of the utmost important parameters to evaluate the repeatability of an explosion process, and the verification criterion on repeatability is commonly set at 5%. From the above statistic, it could be found that both the maximum errors of p max and t a are far less than 5%, namely, the turbulent explosion progress reported by the present article could be believed repeatable with acceptable uncertainty levels.…”
Section: Uncertainty Analysismentioning
confidence: 99%